Impact of microzooplankton grazing on the phytoplankton community in the Kuroshio of the East China sea: A major trophic pathway of the Kuroshio ecosystem. (September 2020) - Kanayama, Takeru; Kobari, Toru; Suzuki, Koji; Yoshie, Naoki; Honma, Taiga; Karu, Fukutaro; Kume, Gen
Abstract: Many foraging fishes spend their vulnerable life stages with low food availability in the oligotrophic Kuroshio. Although they are likely dependent on microbial production as their energy source, there is limited knowledge of the trophodynamics of the planktonic food web in the Kuroshio of the East China Sea (ECS-Kuroshio). Here, we demonstrate energy sources and feeding impacts of microzooplankton on the phytoplankton community based on size-fractionated dilution experiments in the ECS-Kuroshio. Naked ciliates were the most predominant among micro-sized heterotrophs biomass throughout the study area. Pico- to nano-phytoplankton such as Prochlorococcus and haptophytes contributed to total chlorophyll a concentrations. The apparent growth rates in non-diluted bottles without nutrient enrichment were significantly negative for Prochlorococcus and haptophytes. Microzooplankton grazing rates were higher for nano-phytoplankton (0.17–1.45 d −1 ) compared with those for pico- (0.18–1.23 d −1 ) and micro-phytoplankton (0.06–0.92 d −1 ). The community grazing impacts accounted for up to 122% of primary production. These results suggest that one major pathway at lower trophic levels in the ECS-Kuroshio is from pico- and nano-phytoplankton to microzooplankton. This pathway could support energy transfer to higher trophic levels through food resources of mesozooplankton and fish larvae. Highlights: Naked ciliates dominated micro-sized heterotrophs biomass in the Kuroshio. Microzooplankton grazing rates were higher for nano-autotrophs than the other size fractions. Prochlorococcus and haptophytes dominated phytoplankton were grazed by microzooplankton. The community grazing impacts accounted for up to 122% of primary production.